2022
DOI: 10.1109/jstars.2022.3203145
|View full text |Cite
|
Sign up to set email alerts
|

Deep Semantic Segmentation of Trees Using Multispectral Images

Abstract: Forests can be efficiently monitored by automatic semantic segmentation of trees using satellite and/or aerial images. Still, several challenges can make the problem difficult, including the varying spectral signature of different trees, lack of sufficient labelled data, and geometrical occlusions. In this paper, we address the tree segmentation problem using multispectral imagery. While we carry out large-scale experiments on several deep learning architectures using various spectral input combinations, we al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 119 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…A MangroveSeg network based on FAPNet [31] to obtain a mangrove segmentation model using 3002 training images achieved 89.58% overall accuracy, 89.02% precision, and 80.7% mIoU for the testing data. Although the trained mangrove segmentation model can automatically and accurately detect the distribution and area of mangroves from satellite remote sensing images, there are still some limitations in application.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A MangroveSeg network based on FAPNet [31] to obtain a mangrove segmentation model using 3002 training images achieved 89.58% overall accuracy, 89.02% precision, and 80.7% mIoU for the testing data. Although the trained mangrove segmentation model can automatically and accurately detect the distribution and area of mangroves from satellite remote sensing images, there are still some limitations in application.…”
Section: Limitationsmentioning
confidence: 99%
“…Lomeo and Singh [30] designed a mangrove monitoring model for Southeast Asia, in which three types of networks are used to extract mangrove distributions. Ulku et al [31] tested various multispectral remote sensing image and spectral bands using deep semantic segmentation architectures, and it was concluded that combining different categories of multispectral vegetation inDices into a single three-channel input and using state-of-the-art semantic segmentation architectures can improve tree segmentation accuracy under certain conditions. These studies demonstrate the advantages of deep learning frameworks in satellite image processing and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Paired with machine learning automation, studies of long time-series of images can be carried out. Recent improvements in satellite image resolutions (i.e., 0.031 m for the World-View 3 satellite) have allowed for more resolved classification of trees using semantic segmentation neural networks [23,24], detection of individual trees using instance segmentation networks [25][26][27][28] and detection of mangrove forest clearings [29] on highresolution RGB images. Nonetheless, the calculation of certain variables, such as the height of trees extracted from canopy height models (CHMs) is error-prone at the current resolution of satellite imagery and should be paired with low-flying platforms, such as planes or UASs [28] for better validation and performance.…”
Section: Introductionmentioning
confidence: 99%
“…How to interpret large-size and high-resolution remote sensing images automatically, quickly, and efficiently has become a hot issue for research. Among them, the semantic segmentation of remote sensing images plays a vital role in urban planning [1][2][3][4][5], environmental monitoring [6][7][8][9][10], forest and crop analysis [11][12][13][14][15], and smart city construction [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%